Essential role of the G-domain in targeting of the protein import receptor atToc159 to the chloroplast outer membrane - Bauer, Jörg; Hiltbrunner, Andreas; Weibel, Petra; Vidi, Pierre-Alexandre; Alvarez-Huerta, Mayte; Smith, Matthew; Schnell, Danny; Kessler, Félix (My University, 2002)
Two homologous GTP-binding proteins, atToc33 and atToc159, control access of cytosolic precursor proteins to the chloroplast. atToc33 is a constitutive outer chloroplast membrane protein, whereas the precursor receptor atToc159 also exists in a soluble, cytosolic form. This suggests that atToc159 may be able to switch between a soluble and an integral membrane form. By transient expression of GFP fusion proteins, mutant analysis, and biochemical experimentation, we demonstrate that the GTP-binding domain regulates the targeting of cytosolic atToc159 to the chloroplast and mediates the switch between cytosolic and integral membrane forms. Mutant atToc159, unable to bind GTP, does not reinstate a green phenotype in an albino mutant (ppi2) lacking endogenous atToc159, remaining trapped in the cytosol. Thus, the function of atToc159 in chloroplast biogenesis is dependent on an intrinsic GTP-regulated switch that controls localization of the receptor to the chloroplast envelope.
Keywords: Arabidopsis; chloroplast biogenesis; molecular switch; receptor; targeting; GTP; PRECURSOR PROTEINS; ARABIDOPSIS CHLOROPLASTS; ENVELOPE MEMBRANE; TRANSIT SEQUENCE; GTP; TRANSLOCATION; COMPONENTS; MACHINERY; APPARATUS; RECOGNITION